Patents Exploited through Spin-off Formation and Licensing to Established Companies: One University's Decision Making Process - Ismail , Kamariah; Abdul Majid, Izaidin; Wan Omar, Wan Zaidi (2008)
The commercialisation of university patents via spin-off formations or licensing to established companies are the common methods adopted by universities to exploit their patents. This paper looks very closely on who was involved and how the decision was made by one university to patent and to exploit its portfolio of patents.